2016
DOI: 10.5894/rgci596
|View full text |Cite
|
Sign up to set email alerts
|

Temporal evolution of the contamination in the southern area of the Patos Lagoon estuary, RS, Brazil

Abstract: The southern area of the Patos Lagoon estuary has been subjected to intense industrial and port-related activities which have not only caused meaningful changes in the landscape but also degraded aquatic resources by contaminating them with dissolved nutrients and trace metals in the last decades. This study aims at compiling data on the development that has happened in the urban and industrial occupation in Rio Grande, a city located in the south of Rio Grande do Sul, RS, Brazil, by relating it to the main re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…kg-1 ) were found in shelf, beach and nearshore sands, lagoonal/swamp and mangrove sediments of Espírito Santo, Bahia [80] [81], Rio de Janeiro [82] and Rio Grande do Sul states [84]. A significant positive correlation between As and calcium carbonate (r=0.6) could indicate that the calcareous bioclasts participate in metalloid retention and its accumulation in coastal sediments as observed by [81].…”
Section: R Lima Barcellos Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…kg-1 ) were found in shelf, beach and nearshore sands, lagoonal/swamp and mangrove sediments of Espírito Santo, Bahia [80] [81], Rio de Janeiro [82] and Rio Grande do Sul states [84]. A significant positive correlation between As and calcium carbonate (r=0.6) could indicate that the calcareous bioclasts participate in metalloid retention and its accumulation in coastal sediments as observed by [81].…”
Section: R Lima Barcellos Et Almentioning
confidence: 99%
“…Arsenic and Lead enrichment in Brazilian coastal environments were reported in several works as [79]- [84]. High levels of As (i.e.…”
Section: R Lima Barcellos Et Almentioning
confidence: 99%
“…The main inflow of freshwater at the north region comes from the hydrographic basin of the Guaíba system (the Jacuí, Taquarí, Caí, Sinos and Gravataí rivers), supplying 86% of its average total freshwater input. Water discharge of this drainage basin varies from 41 to 22,000 m 3 s -1 (Wallner- Kersanach et al, 2016). It has been estimated a suspended solid discharge from this system in up to 118,130 ton/day (Scotta, 2018).…”
Section: Study Areamentioning
confidence: 99%
“…This river drains the Crystalline Shield consisting of intrusive and metamorphic igneous rocks (Villwock et al, 1972). In the estuarine region, the lagoon receives inflow of the São Gonçalo channel which contribution came from the Mirim lagoon (Wallner-Kersanach et al, 2016). Sediments are mainly from Quaternary formations linked to the evolution or the coastal plain.…”
Section: Study Areamentioning
confidence: 99%
“…Previous studies, identified 22 sites where effluents were discharged; most were industrial and domestic ones (Almeida et al, 1993). A recent study of this environment identified 49 sites where anthropogenic effluents were discharged into this inlet; 49% had contamination levels of organic matter ranging from medium to very strong, mainly from food industries and fertilizer plants (Wallner-Kersanach et al, 2016).…”
Section: Location and Characterization Of The Study Areamentioning
confidence: 99%